Association of mutations in V3/C3 domain with enhanced sensitivity of HIV-1 clade C primary envelopes to autologous broadly neutralizing plasma antibodies. Issue 1 (December 2016) - Deshpande, Suprit; Patil, Shilpa; Kumar, Rajesh; Shrivastava, Tripti; Srikrishnan, Aylur; Murugavel, Kailapuri; Koff, Wayne; Chakrabarti, Bimal; Bhattacharya, Jayanta
Abstract Background Broadly neutralizing antibodies to HIV-1 elicited in infected individuals evolves through shifts in their molecular specificities to viral envelope (Env) in the disease course. Recently, we showed that resistance of circulating HIV-1 clade C to the autologous plasma obtained from one Indian elite neutralizer is associated with mutations in V1 loop. In the present study, we examined the genetic attributes associated with exceptional sensitivity of pseudoviruses expressing anenv gene obtained from the follow up visit contemporaneous plasma of the same donor. Results Examination of chimeric autologous Envs, we found that enhanced neutralization sensitivity is associated with mutations in the V3/C3 region. A positive association between V3/C3 mutation mediated enhanced autologous neutralization of autologous viruses with their sensitivity to both neutralizing and non-neutralizing monoclonal antibodies was found. Interestingly, we found that depletion of autologous plasma with trimeric and monomeric Envs conferred the sensitive Env with resistance indicating that mutations in V3/C3 region altered Env conformation towards optimal exposure of epitopes targeted by the neutralizing and non-neutralizing antibodies. Conclusion In summary, we found distinct vulnerabilities associated with evasion of circulating viruses to broadly neutralizing antibodies mounted in an Indian elite neutralizer.